1998
DOI: 10.1093/humupd/4.4.350
|View full text |Cite
|
Sign up to set email alerts
|

The response of adenomyosis to endometrial ablation/resection

Abstract: Operative hysteroscopy is a relatively new technique that has significantly improved the diagnosis and therapy of abnormal uterine bleeding. At first, the success of operative hysteroscopy in controlling this bleeding seemed extremely high but, with long-term follow-up, a significant failure rate became evident requiring a repeat hysteroscopic procedure or a hysterectomy. Deep adenomyosis is a major cause of these failures. This paper describes three operative ablation techniques and relates many of their fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 26 publications
0
42
0
5
Order By: Relevance
“…In endometrial ablation, the success rate was high at first, but with longterm follow-up a significant failure rate became evident, particularly, in deep adenomyosis. 16 Other conservative surgery has proven to be effective in more than 50% of patients, although no long-term follow-up is currently available. 3 Recently, UAE has been reported as being successful in managing symptoms caused by uterine myomas.…”
Section: Discussionmentioning
confidence: 99%
“…In endometrial ablation, the success rate was high at first, but with longterm follow-up a significant failure rate became evident, particularly, in deep adenomyosis. 16 Other conservative surgery has proven to be effective in more than 50% of patients, although no long-term follow-up is currently available. 3 Recently, UAE has been reported as being successful in managing symptoms caused by uterine myomas.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine adenomyosis, on the other hand, usually requires hysterectomy because of poor results of hormone treatment or endometrial ablation [12]. Several studies have reported symptomatic improvement after UAE in women with uterine leiomyomata and uterine adenomyosis, so investigators have proposed UAE for managing symptomatic uterine adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…Esta diferencia no fue estadísticamente significativa al comparar con aquellas pacientes que no necesitaron segundo procedimiento por SUA, en contraste con otros estudios que proponen a la adenomiosis como causa importante del fracaso de la ablación endometrial histeroscópica (10).…”
Section: Discussionunclassified
“…También se describe en la literatura que la adenomiosis sería una causa importante de falla de la técnica, principalmente aquella que penetra más de 2,5 mm en el espesor miometrial, sin embargo no es considerada una contraindicación propiamente tal (10).…”
Section: Según Los Trabajos De Engelsen Y Cols (13) Yunclassified
See 1 more Smart Citation